Carbon stocks in Danish forest types - Boveland, Judith (SLU/Dept. of Soil and Environment, 2012)
As part of international agreements, countries are now obliged to monitor their greenhouse gas emissions as well as to report their possible sources and sinks. Carbon dioxide is one of the six greenhouse gases listed in the Kyoto Protocol, contributing to global warming. Research is conducted to gain knowledge on how to maximise forest carbon storage capacity, albeit, there are some constraints and limitations to both the role of forests in CO2 mitigation efforts and the estimation and comparison of forest carbon stocks. Forests provide multiple services which might be in conflict to a management strategy solely addressing carbon storage. The estimation and comparison of forest carbon stocks is insofar limited as for instance studies use different definitions for dead wood and different soil depth. With respect to a changing climate, forests are subjected to changes that are not fully predictable yet.